Acute Breathing Infection (ARI) in the Toddlers in the Working Area of Pancasan Health Center, Bogor City, Indonesia - Fathimi Fathimi; Ririn Arminsih Wulandari (JUMP Health (Journal of Ultimate Public Health), 2019)
Introduction: ARI is often misinterpreted as upper respiratory tract infection, whereas ARI does not only attack the upper respiratory tract but also includes the lower respiratory tract. Infection is the entry of germs or microorganisms into the human body and proliferates to cause respiratory tract diseases ranging from the nose to the alveoli and their adnex such as the sinuses, middle ear cavity and pleura. Objective: This study aims to determine the effect of individual and environmental characteristic factors on the incidence of ARI in infants. Method: This study used a cross sectional study design, the number of samples of 163 toddlers, the study location in the work area of the Pancasan Health Center, the time of the study from 27 April to 30 May 2019. Results: The results showed 41.1% of children under five suffered ARI, statistically the variables associated significantly with the incidence of ARI were gender (OR: 2.89) and age (OR: 2.04). Conclusion: Many factors can influence the incidence of ARI in infants, both from the characteristics of children under five, parental characteristics, characteristics of the physical environment of the home and the health service facilities themselves. The next researcher can add research variables, the importance of the role of health workers especially to increase public awareness/ parents in maintaining and maintaining children's health and the existence of cross-program and cross-sector cooperation.